Blue Ridge Heritage Corridor Celebrating Our Past, Creating Our Future - Consortium Press, Appalachian (Appalachian State University, 1997)
The Seventh Biennial Linear Parks Conference was held in Lake Junaluska Assembly, North Carolina, on September 11-13, 1997. Contributors to the proceedings are Kathleen L. Kadlec; Bill Carson; Bill Carson and Judith Francis; Edward J.P. Hauser; Philip A. Grant Jr.; Fred J. Hay; Curt Cottle; Lee R. Skabelund and Lon Williams; Peter Givens; Daniel L. McDonald; Charles E. Roe; Jay Singh; and Donna Warmuth.